2012
DOI: 10.1142/s0192415x12500413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Best Compatibility of Components in Corni Fructus on WT1 Expression in Glomerular Podocytes of Type 2 Diabetic Rats with Early Nephropathy

Abstract: Our previous studies have shown that the best compatibility of components in Corni Fructus (PC) had a protective effect on vascular endothelial cells. In this study, the effect of PC on WT1 expression in glomerular podocytes and the mechanism of PC on early nephropathy in type 2 diabetic rats have been investigated. Type 2 diabetic rats were generated by high-fat diet combined with intraperitoneal injection of 30 mg/kg streptozotocin (STZ), then fed aminoguanidine (100 mg/kg), glimepiride (0.4 mg/kg), low-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Based on some animal experiments investigating the effect of preparations made from C. mas fruits the blood glucose decreasing activity and enhancement of insulin sensitivity were demonstrated (Jayaprakasam et al, 2006; Mirbadalzadeh and Shirdel, 2012; Narimani-Rad et al, 2013; Asgary et al, 2014). The same findings were reported also for fruits of C. officinalis (Park et al, 2011; Gao et al, 2012; Liu et al, 2012; Han et al, 2014). Data from clinical studies evaluating the therapeutic effect of the herbal preparation are available only for C. mas .…”
Section: Similarities and Differences Of Pharmacological Effects Or Bsupporting
confidence: 82%
“…Based on some animal experiments investigating the effect of preparations made from C. mas fruits the blood glucose decreasing activity and enhancement of insulin sensitivity were demonstrated (Jayaprakasam et al, 2006; Mirbadalzadeh and Shirdel, 2012; Narimani-Rad et al, 2013; Asgary et al, 2014). The same findings were reported also for fruits of C. officinalis (Park et al, 2011; Gao et al, 2012; Liu et al, 2012; Han et al, 2014). Data from clinical studies evaluating the therapeutic effect of the herbal preparation are available only for C. mas .…”
Section: Similarities and Differences Of Pharmacological Effects Or Bsupporting
confidence: 82%
“…In addition, alloxan (ALX)-induced mice, db/db mice, KK-Ay mice, and Otsuka Long-Evans Tokushima Fatty (OLETF) rats have been reported for investigation of CMs in DN treatment [ 15 18 ]. Meanwhile, glomerular endothelial cells, mouse podocyte cells, renal proximal epithelial cells, murine hepatocytes, mouse mesangial cells, and human mesangial cells are used as in vitro models for anti-DN mechanism studies [ 19 27 ]. By applying these models, the majority of studies have reported that CMs such as Acacia nilotica pods ( jin - he - huan ) [ 28 ], Artemisia campestris ( huang - ye - hao ) [ 29 ], Paeonialactiflora ( shao - yao ) [ 30 ], and Schisandra chinensis ( wu - wei - zi ) [ 21 , 31 ] exhibited beneficial effects on all stages of experimental DN and may protect multiple organs.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary therapy has been part of TCM for several thousand years. Recent evidence indicates that TCM edible plants such as Panax notoginseng, Cinnamomum zeylanicum and Astragalus membranaceus have significant potential to modulate DN progression Gao et al, 2012;Liu, Xu, Shen, & Wu, 2012;Tang et al, 2011;Tu, Qin, Dong, Lu, & Guan, 2011). Moreover, many TCM edible plants such as mushroom, grape, hawthorn etc., demonstrate a preferable benefit for DN patients Li et al, 2009;Mooradian, Failla, Hoogwerf, Maryniuk, & Wylie-Rosett, 1994).…”
Section: Introductionmentioning
confidence: 99%